Sclerosing Mesenteritis, a Rare Cause of Mesenteric Mass in a Young Adult: A Case Report - Piombino, Eliana; D'Agata, Costanza; Picardo, Maria Carolina; Caltavuturo, Claudia; Magro, Gaetano; Colarossi, Cristina; Memeo, Lorenzo (Frontiers in Surgery, 2021)
Sclerosing mesenteritis (SM) is a rare fibroinflammatory disorder that involves mesenteric adipose tissue, with more frequent localization in the small intestine, with an insidious clinical presentation with symptoms related to mass effect, usually resulting in bowel obstruction, mesenteric ischemia, as well as rapid weight loss. We report a case of 23 years-old male presenting with palpable abdominal mass, mesogastric pain and an history of rapid weight loss, underwent exploratory laparoscopy. A hemorrhagic and gelatinous nodular tumor mass of the mesentery was identified. Histologically, it was composed of a proliferation of bland-looking spindle cells with slightly eosinophilic cytoplasm and elongated normochromatic nuclei with mild nuclear atypia, haphazardly set in a collagenized stroma; fat necrosis and inflammatory cells (lymphocytes, plasma-cells and histocytes) were also evident. The diagnosis of Sclerosing mesenteritis was rendered. Our case emphasizes that histology remains preeminent for a correct diagnosis of SM, being preoperative radiological-based diagnosis non-specific.